Virtual Reality-Based Learning Media Design Training - Astari, Tri (Communautaire: Journal of Community Service, 2022)
This activity aims to facilitate the design of learning media based on Virtual Reality (VR) for educators to be able to present innovative learning in the classroom. The method used in this mentoring activity consists of four stages: Asset Based Community Development called "ABCD". The mentoring training went smoothly even though only 44 participants out of 184 registered. After the participants participated in the mentoring activities, they could conclude that they already had the knowledge and understanding of the suitability of devices that could be used in VR. In addition, participants succeeded in making VR scenes according to the subjects taught in class and tried to implement them for students. Thus, the learning process carried out by participants can continue to experience novelty and innovation